Transcranial Magnetic Stimulation Meets Virtual Reality: The Potential of Integrating Brain Stimulation With a Simulative Technology for Food Addiction - Stramba-Badiale, Chiara; Mancuso, Valentina; Cavedoni, Silvia; Pedroli, Elisa; Cipresso, Pietro; Riva, Giuseppe (Frontiers in Neuroscience, 2020)
The aim of this perspective is to propose and discuss the integration of transcranial magnetic stimulation (TMS) over the dorsolateral prefrontal cortex (DLPFC) with virtual reality (VR) food exposure for therapeutic interventions for food addiction. “Food addiction” is a dysfunctional eating pattern which is typically observed in eating disorders such as bulimia nervosa (BN) and binge eating disorder (BED). Food addiction has been compared to substance use disorder due to the necessity of consuming a substance (food) and the presence of a dependence behaviour. In recent years, VR has been applied in the treatment of eating disorders because it triggers psychological and physiological responses through food exposure in place of real stimuli. VR-Cue exposure therapy (CET) has been proven as a valid technique for regulating anxiety and food craving in eating disorders. More, TMS has been proven to modulate circuits and networks implicated in neuropsychiatric disorders and is effective in treating addiction such as nicotine craving and consumption and cocaine use disorder. The combination of a simulative technology and a neurostimulation would presumably provide better improvement compared to a single intervention because it implies the presence of both cognitive and neuropsychological techniques. The possible advantage of this approach will be discussed in the perspective.